# Long description

Method 1. Radical 33 radical 3 = square root of start expression 33 times 3 end expression = radical 99 = square root of start expression 9 times 11 end expression = radical 9 radical 11 = 3 radical 11. Where, 9 is a perfect square.

Method 2. Radical 33 radical 3 = square root of start expression 33 times 3 end expression = square root of start expression 11 times 3 times 3 end expression = 3 radical 11. Where, 3 times 3 is a perfect square.

Get *Basic Technical Mathematics, 11th Edition* now with O’Reilly online learning.

O’Reilly members experience live online training, plus books, videos, and digital content from 200+ publishers.